2021
DOI: 10.1186/s12954-021-00466-8
|View full text |Cite
|
Sign up to set email alerts
|

Practical implications of naloxone knowledge among suburban people who use opioids

Abstract: Background Naloxone distribution programs have been a cornerstone of the public health response to the overdose crisis in the USA. Yet people who use opioids (PWUO) continue to face a number of barriers accessing naloxone, including not knowing where it is available. Methods We used data from 173 PWUO from Anne Arundel County, Maryland, which is located between Baltimore City and Washington, DC. We assessed the prevalence of recently (past 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Overall, this literature review found that the reported rates of MNA varied widely and have occurred in up to 89% of opioid overdose encounters in the US, were exceptionally high in certain regions, and have increased significantly over time. Among studies that utilized EMS data, MNA rates ranged from 9% to 53%, 16 22 while studies based on bystander-reported data were notably higher, ranging from 16% to 89% 23 29 . The wide range in reported MNA rates overall is not surprising given the significant variation in study design and attributes, the different data sources utilized, the year and geography studied, and the difficulty and limitations in accurately capturing this data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this literature review found that the reported rates of MNA varied widely and have occurred in up to 89% of opioid overdose encounters in the US, were exceptionally high in certain regions, and have increased significantly over time. Among studies that utilized EMS data, MNA rates ranged from 9% to 53%, 16 22 while studies based on bystander-reported data were notably higher, ranging from 16% to 89% 23 29 . The wide range in reported MNA rates overall is not surprising given the significant variation in study design and attributes, the different data sources utilized, the year and geography studied, and the difficulty and limitations in accurately capturing this data.…”
Section: Discussionmentioning
confidence: 99%
“…With the increase of synthetic opioids and the rapid onset of effect, evidence is emerging suggesting the need for increased doses of naloxone to reverse opioid toxicity. Numerous studies have been published examining the occurrence of multiple naloxone administrations (MNA) in opioid overdose reversals, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] however, these studies have varied in study design, scientific rigor, sample size and geographic locations, making it difficult to obtain a comprehensive understanding of the frequency and trends of MNA occurrence in the US.…”
Section: Introductionmentioning
confidence: 99%
“…Our review revealed the lack of literature that focused on inequity associated with opioid-related health outcomes or strategies to minimize barriers and promote access by the vulnerable groups who are disproportionately experiencing opiate-related harms, including individuals with disabilities and without accessible means of transportation [67], as well as low-income individuals, particularly those without stable housing [36,74]. These vulnerable groups reported barriers related to the varying number of nearby community pharmacies with naloxone distribution programs in different areas [34,65] or the loss of naloxone kits during transient housing [74]. A study conducted by Mitchell et al (2017) underscored the need for the placement of naloxone kits in common spaces of low-income housing in order to facilitate better access to naloxone by the marginalized populations [16].…”
Section: Barriers To Ease Of Access For Vulnerable Populationsmentioning
confidence: 99%
“…A study conducted by Mitchell et al (2017) underscored the need for the placement of naloxone kits in common spaces of low-income housing in order to facilitate better access to naloxone by the marginalized populations [16]. Not being aware of naloxone programs, not having previously accessed naloxone, and not having knowledge of multiple sources of naloxone were found to negatively impact access [65]. Furthermore, our review revealed various studies of naloxone programs in North America, including North Carolina [63,67], Massachusetts, and Rhode Island in the United States [46], as well as Alberta [41] and British Columbia in Canada [16,74].…”
Section: Barriers To Ease Of Access For Vulnerable Populationsmentioning
confidence: 99%
“…Structural barriers such as inaccessibility and a lack of knowledge about where to obtain naloxone, particularly for rural residents [ 25 , 72 ], and the stigma ascribed to PWUOs deter people from obtaining naloxone [ 5 , 70 ]. Rural residents confront additional barriers because some pharmacists are unable or unwilling to stock naloxone, and rural residents who do obtain it have been found to receive less comprehensive administration instructions than urban residents [ 72 ].…”
Section: Introductionmentioning
confidence: 99%